2019
DOI: 10.3389/fmars.2019.00402
|View full text |Cite
|
Sign up to set email alerts
|

Present-Day Distribution and Potential Spread of the Invasive Green Alga Avrainvillea amadelpha Around the Main Hawaiian Islands

Abstract: Algal assemblages are critical components of marine ecosystems from the intertidal to mesophotic depths; they act as primary producers, nutrient cyclers, and substrate providers. Coral reef ecosystems can be disrupted by stressors such as storm events, effluent inundation, sudden temperature shifts, and non-native invaders. Avrainvillea amadelpha is an invasive green alga that was first recorded in the main Hawaiian Islands on the west shore of Oahu and has continued to be of concern due to its extreme competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Each species was modeled individually using two machine learning algorithms and two regression algorithms: random forests (RFs, machine learning; Breiman, 2001), boosted regression trees (BRTs, machine learning; Elith et al, 2008), generalized linear models (GLMs, regression;McCullagh, 1984) and generalized additive models (GAMs, regression;Hastie and Tibshirani, 2014). All these algorithms showed good performances when modeling niches or species distributions in past similar applications (e.g., Chefaoui et al, 2017;Veazey et al, 2019;Morato et al, 2020) and are available on the "BIOMOD2" framework. Readers are referred to the cited original descriptions for more information about each algorithm.…”
Section: Modeling Proceduresmentioning
confidence: 99%
“…Each species was modeled individually using two machine learning algorithms and two regression algorithms: random forests (RFs, machine learning; Breiman, 2001), boosted regression trees (BRTs, machine learning; Elith et al, 2008), generalized linear models (GLMs, regression;McCullagh, 1984) and generalized additive models (GAMs, regression;Hastie and Tibshirani, 2014). All these algorithms showed good performances when modeling niches or species distributions in past similar applications (e.g., Chefaoui et al, 2017;Veazey et al, 2019;Morato et al, 2020) and are available on the "BIOMOD2" framework. Readers are referred to the cited original descriptions for more information about each algorithm.…”
Section: Modeling Proceduresmentioning
confidence: 99%
“…It is likely that an increase in water flow will cause greater dilution of the oxidant and thus make the reaction time shorter. However, it is suggested that the regions exposed to minimal bottom currents are most susceptible to invasion (Veazey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A . lacerata has now spread into shallow waters in recent decades from deeper habitats [ 2 , 5 , 6 , 7 ]. More recently, Avrainvillea erecta (Berkeley) A.Gepp & E.S.Gepp has been recorded on O‘ahu and Maui as an introduced species, and continues to rapidly increase in abundance and distribution [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The origins of the Hawaiian populations of the green alga, A. lacerata, are unknown; some possibilities include that the alga is an indigenous member to the flora or an early introduction before collections of even shallow water algae were first made in about 1826 [4]. A. lacerata has now spread into shallow waters in recent decades from deeper habitats [2,5,6,7]. More recently, Avrainvillea erecta (Berkeley) A.Gepp & E.S.Gepp has been recorded on O'ahu and Maui as an introduced species, and continues to rapidly increase in abundance and distribution [6].…”
Section: Introductionmentioning
confidence: 99%